A New Computerized Program for Surveillance of Prosthetic Arteriovenous Fistulas. Issue 1 (2015) - Tozzi, Matteo; Franchin, Marco; Formica, Vincenzo; Ganna, Matteo; Piffaretti, Gabriele
Stenosis and thrombosis are common causes of prosthetic vascular access (pVA) failure. The role of arteriovenous fistula (AVF) surveillance is widely debated. The aim of this paper is to present a new real-time application designed for AVF surveillance called SPIDER. Surgical staff and hemodialysis nurses are responsible for data entry. SPIDER automatically analyses data and generates alerts in case of abnormal trends. Surgical evaluation and duplex Doppler ultrasonography are then immediately performed to confirm presence of stenosis or other possible pVA defects. Surgery can be performed if required. A preliminary analysis of results will be completed at 12 months after the program begins and subsequently after 24 months. Primary assisted patency will be compared with historical using multivariate analysis. Expected results are an improvement in primary assisted pVA patency and reduction of hospitalizations. Simultaneous management of a high number of patients can become difficult due to the large amount of data required for surveillance. We want to demonstrate whether a real-time automated system could help to prevent thrombosis and graft loss.